Systematic Sorting: Teacher Characteristics and Class Assignments. (April 2013) - Kalogrides, Demetra; Loeb, Susanna; Béteille, Tara
Although prior research has documented differences in the distribution of teacher characteristics across schools serving different student populations, few studies have examined the extent to which teacher sorting occurs within schools. This study uses data from one large urban school district and compares the class assignments of teachers who teach in the same grade and in the same school in a given year. The authors find that less experienced, minority, and female teachers are assigned classes with lower achieving students than are their more experienced, white, and male colleagues. Teachers who have held leadership positions and those who attended more competitive undergraduate institutions are also assigned higher achieving students. These patterns are found at both the elementary and middle/high school levels. The authors explore explanations for these patterns and discuss their implications for achievement gaps, teacher turnover, and the estimation of teacher value-added.